2021
DOI: 10.1021/acsomega.1c02569
|View full text |Cite
|
Sign up to set email alerts
|

CpACpP: In Silico Cell-Penetrating Anticancer Peptide Prediction Using a Novel Bioinformatics Framework

Abstract: Cell-penetrating anticancer peptides (Cp-ACPs) are considered promising candidates in solid tumor and hematologic cancer therapies. Current approaches for the design and discovery of Cp-ACPs trust the expensive high-throughput screenings that often give rise to multiple obstacles, including instrumentation adaptation and experimental handling. The application of machine learning (ML) tools developed for peptide activity prediction is importantly of growing interest. In this study, we applied the random forest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 73 publications
0
11
0
Order By: Relevance
“…In the feature generation process, we used iFeature (Chen et al, 2018) and Pfeature (Pande et al, 2019), two publicly available Python‐based toolkits that are capable of generating a comprehensive spectrum of descriptors, to facilitate the numerical representation of biological sequences for ML purposes. These sequence‐based and length‐independent features incorporate various properties of proteins such as the composition of atoms, bonds, amino acids, and dipeptides, as well as physico‐chemical properties, repeats, distribution, etc., and have been used in previous studies (Ariaeenejad et al, 2018; Nasiri et al, 2021). Many of the generated descriptors were duplicates and thus were removed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the feature generation process, we used iFeature (Chen et al, 2018) and Pfeature (Pande et al, 2019), two publicly available Python‐based toolkits that are capable of generating a comprehensive spectrum of descriptors, to facilitate the numerical representation of biological sequences for ML purposes. These sequence‐based and length‐independent features incorporate various properties of proteins such as the composition of atoms, bonds, amino acids, and dipeptides, as well as physico‐chemical properties, repeats, distribution, etc., and have been used in previous studies (Ariaeenejad et al, 2018; Nasiri et al, 2021). Many of the generated descriptors were duplicates and thus were removed.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, data science revolutions have a great effect on conventional enzyme research and could speed up enzyme discovery procedure. ML may play a central role in the paradigm change away from using traditional methods in different applications such as peptide function prediction (Atanaki et al, 2020;Kavousi et al, 2020;Nasiri et al, 2021), enzyme characteristics prediction (Ariaeenejad et al, 2018(Ariaeenejad et al, , 2021Shahraki et al, 2019aShahraki et al, , 2020, and so on. In a review done by Toyao et al (Toyao et al, 2020), recent developments have been reported in the use of ML to build homogeneous and heterogeneous catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…123 The safety, side effects and effectiveness of carrier peptides that target cancer cells directly and/or by activating immune responses have been widely confirmed in clinical trials. 124,125 Vaccine peptide…”
Section: Anti-cancer Peptidesmentioning
confidence: 99%
“…Compared with conventional chemotherapy drugs, ACPs show better performances in inhibiting the proliferation and migration of tumour cells and tumour blood vessels 123 . The safety, side effects and effectiveness of carrier peptides that target cancer cells directly and/or by activating immune responses have been widely confirmed in clinical trials 124,125 …”
Section: Cpps and Anti‐cancer Cargoes Deliverymentioning
confidence: 99%
“…Owing to the failure of current chemotherapeutic mechanisms and their associated health risks, hopes were given up with regard to the treatment of resistant cancer cells . The amphipathic anticancer peptides (ACPs) that selectively target the cell survival signaling are potentially attractive for clinical use. However, the hydrolytic instability of ACPs along with the altered composition of the cell membrane and defects in the apoptotic machinery may result in peptide ineffectiveness. , In this regard, the redox imbalance or impaired metabolic homeostasis induced by the in vitro self-assembling of ACPs and their accumulation in the endoplasmic reticulum (ER) or inside the mitochondria are considered suitable to treat the resistant cancer cells. ,, Alternatively, the caspase-independent necroptotic or autophagic deaths promoted by the ACP nanostructures via targeting the Golgi apparatus and ER membrane systems are privileged for the selective toxicity. …”
Section: Introductionmentioning
confidence: 99%